Evaluation of the reform and rehabilitation diploma program in the Training and Development Center of reform and rehabilitation centers in Jordan from the viewpoint of learners and faculty members (Journal of the College of Basic Education, 2022)
The study aimed to evaluate the reform and rehabilitation diploma program in the Training and Development Center of reform and rehabilitation centers in Jordan towards the program from the point of view of learners and faculty members. The study personnel consisted of (50) non-commissioned officers affiliated with the Public Security in Jordan. The researcher developed the study tool and verified the indications of its validity and stability. Arithmetic means, t-test, one-way analysis of variance and Scheffe test for post comparisons were used to answer the study questions. The results of the study indicated that the estimates fell within the average level. And that there are differences in the dimension of the program and total content and in favor of the Tawjihi, and there are no differences attributable to the military rank, and there are differences in the dimension of the roles of the center and total management due to the variable of age. The study ended with recommendations related to the study problem.